2007
DOI: 10.1080/14622200701239621
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity and early relapse to smoking: A test among Mexican daily, low-level smokers

Abstract: The aim of the present investigation was to extend previous work on anxiety sensitivity (AS) and early smoking relapse among a sample of 130 (74 females) young adult (M (age) = 22.5 years, SD = 2.1) daily low-level smokers (9.3 cigarettes/day, SD = 11.5) from Mexico City, Mexico. Results indicated that of the global-level and lower-order factors (i.e., physical, mental incapacitation, and social concerns) on the Anxiety Sensitivity Index, only the physical concerns factor was significantly related to early lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 63 publications
3
38
1
Order By: Relevance
“…Nevertheless, this work complements and extends existing work on the role of anxiety sensitivity in cessation, which suggests that tendency to catastrophize about internal sensations (i.e., score high on anxiety sensitivity measures) is uniquely associated with smoking to reduce negative affect, decreased cessation self-efficacy, and increased risk of early cessation relapse Zvolensky et al 2007). Consistent with this, the present study found that individuals who appraised cravings as meaning something negative about themselves or who believed their craving-related thoughts needed to be controlled felt more depressed and less confident in their ability to abstain from smoking.…”
Section: Variablesmentioning
confidence: 50%
“…Nevertheless, this work complements and extends existing work on the role of anxiety sensitivity in cessation, which suggests that tendency to catastrophize about internal sensations (i.e., score high on anxiety sensitivity measures) is uniquely associated with smoking to reduce negative affect, decreased cessation self-efficacy, and increased risk of early cessation relapse Zvolensky et al 2007). Consistent with this, the present study found that individuals who appraised cravings as meaning something negative about themselves or who believed their craving-related thoughts needed to be controlled felt more depressed and less confident in their ability to abstain from smoking.…”
Section: Variablesmentioning
confidence: 50%
“…Collectively, a variety of studies are consistent with the emerging perspective that distress tolerance is an important factor in smoking lapse. Such a conclusion is strengthened by research that suggests parallel psychological constructs such as sensitivity to anxiety-related states (anxiety sensitivity; Brown, Kahler, Zvolensky, et al, 2001 ;Zvolensky et al, 2007 ), a tendency to avoid emotional states (e.g., thought or emotional suppression; Hayes, Wilson, Gifford, Follette, & Strosahl, 1996 ;Salkovskis & Reynolds, 1994 ), and emotional reactivity ( Zvolensky, Feldner, Eifert, & Brown, 2001 ) may be related to problems in quitting successfully.…”
Section: Introductionmentioning
confidence: 99%
“…These models are consistent with research on the importance of anxiety sensitivity, distress tolerance and acceptance during cessation. For example, self-reported discomfort with anxiety-related physical sensations and behavioral difficulty persisting with uncomfortable physiological and cognitive challenge tasks (e.g., CO 2 inhalation, speeded mental arithmetic) predict early relapse from smoking cessation (Brandon et al, 2003;Brown, Kahler, Zvolensky, Lejuez, & Ramsey, 2001;Brown, Lejuez, Kahler, & Strong, 2002;Zvolensky et al, 2007).…”
mentioning
confidence: 98%